OvipositionPreference of the Crop Moth Crocidolomia Pavonana Zeller in Several Host Plants of the Brassicacea Family in Tomohon City - Sherlij Dumalang; Maxi Lengkong (Postgraduate, University of Mataram, 2026)
The phenomena and problems associated with various control strategies require solutions and answers to ensure control techniques through a deep understanding of the phenotypic appearance and behavior of target pests. The objectives of this study were: (1) to determine the oviposition preference patterns of female Crocidolomia pavonana Zell. on several types of vegetable plants from the Brassicaceae family, (2) to analyze the differences in the number of eggs laid by C. pavonana on each host plant tested, including determining the most preferred plant for oviposition. The study was conducted in a laboratory using a Latin Square Design (LSD), with 3 treatments and 3 replicates. The sample consisted of 15 pairs of adult insects (moths),placed in the cage. Each cage contain 5 pairs of moths in the same age and three types of host plants; mustard greens, mostar, and Chinese cabbage, with 5 pairs of imagoes placed in each cage. The results showed that oviposition preferences of C. pavonana influenced by the type of host plant, with mustard and cabbage tending to be preferred over Chinese cabbage. There were differences in the average number of eggs laid by female C. pavonana, namely on mustard greens (33.2 eggs), mostar (45.2 eggs), and Chinese cabbage (38.2 eggs).